Current Challenges in Studying Alternative Splicing in Plants: The Case of Physcomitrella patens SR Proteins - Melo, José Pedro; Kalyna, Maria; Duque, Paula (Frontiers in Plant Science, 2020)
To colonize different terrestrial habitats, early land plants had to overcome the challenge of coping with harsh new environments. Alternative splicing — an RNA processing mechanism through which splice sites are differentially recognized, originating multiple transcripts and potentially different proteins from the same gene — can promote plant stress tolerance. Serine/arginine-rich (SR) proteins constitute an evolutionarily conserved family of major alternative splicing regulators that in plants subdivides into six subfamilies. Despite being well studied in animals and a few higher plants, such as the model species Arabidopsis thaliana and the crop Oryza sativa, little is known of these splicing factors in early land plants. Establishing the whole complement of SR proteins in different species is essential to understand the functional and evolutionary significance of alternative splicing. An in silico search for SR proteins in the extant moss Physcomitrella patens revealed inconsistencies both in the published data and available databases, likely arising from automatic annotation lacking adequate manual curation. These misannotations interfere with the description not only of the number and subfamily classification of Physcomitrella SR proteins but also of their domain architecture, potentially hindering the elucidation of their molecular functions. We therefore advise caution when looking into P. patens genomic resources. Our systematic survey nonetheless confidently identified 16 P. patens SR proteins that fall into the six described subfamilies and represent counterparts of well-established members in Arabidopsis and rice. Intensified research efforts should disclose whether SR proteins were already determining alternative splicing modulation and stress tolerance in early land plants.